2007
DOI: 10.1002/ceat.200700330
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Nickel and Boron from Plating Rinse Effluent by Electrochemical and Chemical Techniques

Abstract: In this work, electrotreatment of nickel and boron containing plating rinse effluents was studied with mild steel and aluminum electrodes. Industrial effluent treatment directly by an electrochemical technique is capable of removing 80-85 % nickel. The residual nickel interfered with boron determination by curcumin method. The pH fall during electrotreatment in industrial effluent is due to electrodeposition of nickel at the cathode surface, evidenced by simulated effluent treatment. Nickel concentration can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Adhoum et al [30] and Colder et al [39] used current densities between 8 and 48 mA/cm 2 and demonstrated that the increase of applied current density enhanced the treatment rate resulting in a faster removal of pollutants. Table 3 shows the effect of applied current density on following parameters, such as the removal rate of nickel, solution pH, amount of generated sludge, electrical energy consumption and concentration of aluminium in the treated solution, versus time of electrolysis.…”
Section: Applied Current Densitymentioning
confidence: 99%
“…Adhoum et al [30] and Colder et al [39] used current densities between 8 and 48 mA/cm 2 and demonstrated that the increase of applied current density enhanced the treatment rate resulting in a faster removal of pollutants. Table 3 shows the effect of applied current density on following parameters, such as the removal rate of nickel, solution pH, amount of generated sludge, electrical energy consumption and concentration of aluminium in the treated solution, versus time of electrolysis.…”
Section: Applied Current Densitymentioning
confidence: 99%
“…Sludge generation was about 0.44 and 0.49 g with the Al electrode. It is reported in the literature 24 that nickel deposition on the cathode is responsible for the fall of pH during electrotreatment. Cu plating rinse water treatment shows the reverse trend in pH profile.…”
Section: Resultsmentioning
confidence: 98%
“…3) is comparable with the results obtained during electrolysis of pretreated nickel plating effluent. 24 Industrial copper plating rinse effluent collected for the present investigation contained about 6.8 mg L −1 initial Zn concentration (Table 1). It was noted that within the first 10 min of treatment, Zn concentration fell below its discharge limit (4 mg L −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…[1] Due to its cost, it is incentive to recover it from waste solutions. There are many technologies involving chemical and physical processes which have been developed over the past years to remove hazardous metal ions, such as chemical precipitation, [2,3] adsorption, [4][5][6][7][8][9][10][11][12] ion exchange, [13,14] electrochemical technique, [15][16][17] , and membrane processes, [18][19][20] ; however, all of them have drawbacks. Chemical precipitation requires extremely long settling time and produces a large amount of sludge; ion exchange and adsorption are expensive and require frequent regeneration; and membrane processes suffer from operational problems due to fouling of membranes which can be reduced by several approaches, e.g., by feed pretreatment and treatment of the membrane surface.…”
Section: Introductionmentioning
confidence: 99%